Effects of a tiered competence-based simulation educator development program. (February 2022) - Roh, Young Sook; Issenberg, S. Barry
Abstract: Aim: This study aimed to develop and identify the effects of a tiered competence-based simulation educator development program on knowledge, competence and attitudes. Background: Competence and educational needs-based training is required to improve nursing simulation educators' learning outcomes. Design: This study used a one-group pretest–posttest design. Methods A convenience sample of 65 nursing simulation educators completed a self-administered questionnaire. Three levels of training programs were implemented: basic, intermediate and advanced courses. The pretest–posttest differences in knowledge, competence and attitude scores were analyzed using the paired t -test. The main variable scores for the three programs were compared using one-way ANOVA and the Scheffé post hoc test. Results: Posttest levels of knowledge, competence and attitudes were higher than the pretest measures. Simulation educators in the basic course reported greater improvements in perceived competence when compared with participants in the intermediate course. Conclusions: The tiered competence-based simulation educator development program improved nursing simulation educators' knowledge, competence and attitudes across all course levels. Highlights: Competence-based training is required to improve simulation educators' competence. Posttest level of knowledge, competence, and attitudes were significantly increased. The program had positive effects on improving knowledge, competence, and attitudes.